Pembelajaran Biopreneu r E-Learning Cisco Webex Meeting Ditinjau dari Sikap Siswa SMA - Subhan Harie; Fitria Sari Hasanusi; Ari Wahyu Leksono (Jurnal Ilmiah Wahana Pendidikan, 2020)
Online learning in the days of the pandemic corona is very important. Besides being able to be an alternative learning, such as Cisco Webex should be used for distance learning. The purpose of this study was to assess and describe the learning biopreneur e learning cisco webex meeting in terms of the attitudes of high school students. The student population is 120 students, while the sample is 30 students. The team gives questionnaires, and holds special interviews to students. The research activities took place from the beginning of August 2019 until December 2020. This study used a qualitative descriptive methodology. The results show that students are more enthusiastic and get more attention, because students can learn more independently and efficiently. In terms of time students can freely study at home, but there are some obstacles such as adjusting the schedule and how to use the Cisco program system that is not familiar to some students.